Catalytic conversion of gaseous tars using land, coastal and marine biomass-derived char catalysts in a bench-scale downstream combined fixed bed system. (May 2020) - Li, Jie; Liu, Zhengyi; Tian, Yuanyu; Zhu, Yanan; Qin, Song; Qiao, Yingyun
Graphical abstract: Highlights: Tar catalytic reforming behaviors of biochar catalysts were critically compared. The tar conversion efficiency could reach about 94.6% by Re-char catalyst. The yield and compositions of gas products also changed markedly. Attempt to propose the mechanism of tar reduction process over biochar catalysts. The increase in temperature can promotes the polymerization of some tar components. Abstract: The catalytic activity of biochar for tar removal was evaluated in a bench-scale combined fixed bed reactor by comparison of gaseous tar catalytic cracking behaviors over land (Corn stalks, Cs), coastal (Reed, Re) and marine ( Sargassum horneri, Sh) char catalyst. The experiments demonstrated that the tar yield after addition of the biochar was reduced significantly; the tar conversion efficiency reached to 94.6% for catalytic at 850 °C with 50 mm char bed length using Re char. And the yield and composition of gas also changed markedly. The percentage of H2 and CO in the product gas were obviously increased. Sh has a higher H2 content (49.3% of the total gas content), whereas, CO dominated in the gas products for Cs (45.4%) and Re (48.1%). The results from GC–MS analysis illustrated that the increase in temperature promoted the tar cracking and also promotes the polymerization of some tar components.